Effects of a 16-week training proposal focused on the stride technique on the kinematic characteristics of the sports gesture in the long-distance race in athletes from the Universidad Libre (Bogotá-Colombia) (Impetus, 2022)
This article aims to show the incursion of a 16-week training plan focused on the stride technique in a group of long-distance athletes from the Universidad Libre. For this, 20 athletes divided into two groups were selected: 10, called the experimental group (EG) to whom the training plan was applied and 10 as the control group (CG), evaluated in two moments, pre and post. The test used to measure these two moments consisted of a one kilometer race in which the personal brand was analyzed, a kinematic study of the phases of the stride technique and a resistance and power test; the results obtained from the two groups were compared to evaluate the achievements obtained in this study.